The elements of news writing - Kershner, James W., ....- (London : Allyn and Bacon, 2012)
Kershner's The Elements of News Writing 3/e is a concise handbook that presents the essential rules of journalism, while offering in-depth analysis of the evolving industry. With comprehensive coverage from history to how-to, and discussions of new media, online journalism, blogging, and social networking, this text covers news writing from a 360 degree view. The Elements of News Writing covers the basics of news writing without the extra verbiage. The author pays extra attention to grammar and usage, with easy-to-follow basic tips on writing forall types of mass media, new and old.
Keywords: Journalistiek